MLL-ENL Inhibits Polycomb Repressive Complex 1 to Achieve Efficient Transformation of Hematopoietic Cells - Mäthner, Emanuel; Garcia-Cuellar, Maria-Paz; Breitinger, Constanze; Takacova, Sylvia; Divoky, Vladimir; Hess, Jay L.; Slany, Robert (Cell Reports, 2013)
Stimulation of transcriptional elongation is a key activity of leukemogenic MLL fusion proteins. Here, we provide evidence that MLL-ENL also inhibits Polycomb-mediated silencing as a prerequisite for efficient transformation. Biochemical studies identified ENL as a scaffold that contacted the elongation machinery as well as the Polycomb repressive complex 1 (PRC1) component CBX8. These interactions were mutually exclusive invitro, corresponding to an antagonistic behavior of MLL-ENL and CBX8 invivo. CBX8 inhibited elongation in a specific reporter assay, and this effect was neutralized by direct association with ENL. Correspondingly, CBX8-binding-defective MLL-ENL could not fully activate gene loci necessary for transformation. Finally, we demonstrate dimerization of MLL-ENL as a neomorphic activity that may augment Polycomb inhibition and transformation. © 2013 The Authors.